2013
DOI: 10.1016/j.scitotenv.2013.03.088
|View full text |Cite
|
Sign up to set email alerts
|

Performance of UK wastewater treatment works with respect to trace contaminants

Abstract: This study examined the performance of 16 wastewater treatment works to provide an overview of trace substance removal in relation to meeting the objectives of the Water Framework Directive (WFD). Collection and analysis of over 2,400 samples including sewage influent, process samples at different stages in the treatment process and final effluent has provided data on the performance of current wastewater treatment processes and made it possible to evaluate the need for improved effluent quality. Results for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 33 publications
(49 reference statements)
2
88
1
2
Order By: Relevance
“…Electrochemical treatment (EC) (7), alters the surface charge on contaminant particles held in the water causing them to separate and accumulate in an easily removable mass. A comprehensive study of the performance of UK wastewater treatment plants 42 highlighted a wide variation in removal rates of between 25-79% for heavy metals. This variation was attributed to variations in composition of wastewater being treated and the operation parameters at individual treatment works.…”
Section: Treatment Of Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical treatment (EC) (7), alters the surface charge on contaminant particles held in the water causing them to separate and accumulate in an easily removable mass. A comprehensive study of the performance of UK wastewater treatment plants 42 highlighted a wide variation in removal rates of between 25-79% for heavy metals. This variation was attributed to variations in composition of wastewater being treated and the operation parameters at individual treatment works.…”
Section: Treatment Of Heavy Metalsmentioning
confidence: 99%
“…This variation was attributed to variations in composition of wastewater being treated and the operation parameters at individual treatment works. 42 Removal of trace metals dissolved in solution currently pose the most significant challenge to the industry in comparison to other trace contaminants, so it will be pertinent to consider the contribution shale gas operations may make to the waste load requiring treatment in future work. However, in this work, due the limited dataset available from UK operations at present, we focus on assessing options for treatment of the two major problem contaminants in UK FP waters; salinity and NORM.…”
Section: Treatment Of Heavy Metalsmentioning
confidence: 99%
“…A total of 70 determinants were targeted, 64 of which were trace contaminants situation. Results obtained have contributed with useful findings and provided a deeper insight of the current status of the sector [2][3][4]. The substantive and diverse data this study has generated has been used for guiding rational decision making within the water industry [78].…”
Section: Cip As An Example Of Decision Challengementioning
confidence: 76%
“…BPA can also partially accumulate by passing through soil and river sediments. [15] 60-600 [43] 360-1620 [18] 378-890 [9] 416-2050 [23] 1800 [40] 2-44 [43] 30-1100 [15] 35-86 [23] 110-300 [18] 700 [40] 1.2-1900 [1] 2.1-87 [13] 2.2-4230 [21] 6-34 [23] 6-68 [11] 6-500 [26] 6-881 [22] 7.5-334 [12] 55-162 [27] 192-215 [15] 460-4800 [25] b.l.q.-494 [17] b.l.q.-7000 [19] b.l.q.-9300 [28] 1-1136 [20] 1-11 [4] 79-2550 [15] 600-11000 [14] 0.17-1.25 [2] 0.58-36700 [8] 1.1-43 [42] 4.3-130 [25] 10-530 [23] 53-196 [43] 0.32 [6] Fu and Kawamura [5] showed that bisphenol A is also present in air samples. In the agricultural areas of China, its concentration in the air does not exceed 240 pg/m3, but the air samples in urban areas are more contaminated (20-2.340 pg/m 3 ).…”
Section: Occurrence In the Environmentmentioning
confidence: 99%